Cultural appropriation in Messiaen’s rhythmic language - Oliver, D (2016)
Bruhn (2008) and Griffiths (1978) have referred in passing to Messiaen’s use of non-Western content as an appropriation, but a consideration of its potential moral and aesthetic failings within the scope of modern literature on artistic cultural appropriation is an underexplored topic. Messiaen’s first encounter with India came during his student years, by way of a Sanskrit version of Saṅgītaratnākara (c. 1240 CE) written by the thirteenth-century Hindu musicologist Śārṅgadeva. I examine Messiaen’s use of Indian deśītālas within a cultural appropriation context. Non-Western music provided a safe space for him to explore the familiar, and served as validation for previously held creative interests, prompting the expansion and development of rhythmic techniques from the unfamiliar. Chapter 1 examines the different forms of artistic cultural appropriation, drawing on the ideas of James O. Young and Conrad G. Brunk (2012) and Bruce H. Ziff and Pratima V. Rao (1997). I consider the impact of power dynamic inequality between ‘insider’ and ‘outsider’ cultures. I evaluate the relation between aesthetic errors and authenticity. Chapter 2 considers the internal and external factors and that prompted Messiaen to draw on non-Western rhythm. I examine Messiaen’s appropriation of Indian rhythm in relation to Bloomian poetic misreading, and whether his appropriation of Indian rhythm reveals an authentic intention. Chapter 3 analyses Messiaen’s interpretation of Śārṅgadeva’s 120 deśītālas and its underlying Hindu symbolism. Chapter 4 contextualises Messiaen’s Japanese poem Sept haïkaï (1962) in relation to other European Orientalist artworks of the late-nineteenth and early-twentieth centuries, and also in relation to Michael Sullivan’s (1987: 209) three-tiered definitions of japonism. .